Case series of congenital heterotopic neuroglial tissue in the parapharyngeal space. (July 2016) - Chen, Daniel; Dedhia, Kavita; Ozolek, John; Mehta, Deepak
Abstract: Cases of congenital heterotopic tissue presenting in the head and neck are frequent in the pediatric otolaryngology literature. Heterotopic glioneuronal tissue is rare and fewer than 20 cases of heterotopic glioneuronal tissue in the parapharyngeal space have been reported. We present two cases of infant children who were seen at the Children's Hospital of Pittsburgh in 2013 with glioneuronal heterotopic masses in the parapharyngeal space.